Applications of Graphene Oxide (Go) and Its Hybrid with Nanoparticles for Water Decontamination - Sepúlveda-Ortiz, P; Sepúlveda-Ortiz, P (Elsevier, 2022)
The use of two-dimensional materials (2DM), specifically graphene oxide (GO) and nanoparticles (metallic and oxides) are one category of advanced materials that are currently applied to different fields, this, attributed to their different physicochemical properties. Specifically, the application of metallic and oxide nanoparticles (NPs) has had interest in water remediation. However, the use of hybrid nanomaterials, such as GO-NPs, has shown better performance to remove pollutants (organic and inorganic), viruses and bacteria from aqueous matrices. In this context, in this chapter the use of GO and hybrid nanomaterial of GO-NPs to removed organic and inorganic pollutant from water by means different process and the elimination of viruses and bacteria by the photocatalysis process in the water disinfection is shows. © 2022 Elsevier Inc. All rights reserved.